2006
DOI: 10.1115/1.2437781
|View full text |Cite
|
Sign up to set email alerts
|

Film Effectiveness Performance of an Arrowhead-Shaped Film-Cooling Hole Geometry

Abstract: This paper presents the first experimental and numerical work of film effectiveness performance for a novel film-cooling method with an arrowhead-shaped hole geometry. Experimental results demonstrate that the proposed hole geometry improves the film effectiveness on both suction and pressure surface of a generic turbine airfoil. Film effectiveness data for a row of the holes are compared to that of fan-shaped holes at the same inclination angle of 35 deg to the surface on a large-scale airfoil model at engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The highest performance in the stream-wise and span-wise directions was shown to be at 0.5 blowing ratio and it decreased with further increasing in blowing ratio. Okita and Nishiura [21] studied the film cooling effectiveness performance of arrowhead fan shaped hole (AFH) and fan shaped hole with laidback (FSH) geometries on pressure and suction sides of airfoil. From their results, the AFH provided higher film cooling effectiveness at high blowing ratios (Br > 1.5) than the FSH on the suction side of the airfoil.…”
Section: Subscripts and Superscriptsmentioning
confidence: 99%
“…The highest performance in the stream-wise and span-wise directions was shown to be at 0.5 blowing ratio and it decreased with further increasing in blowing ratio. Okita and Nishiura [21] studied the film cooling effectiveness performance of arrowhead fan shaped hole (AFH) and fan shaped hole with laidback (FSH) geometries on pressure and suction sides of airfoil. From their results, the AFH provided higher film cooling effectiveness at high blowing ratios (Br > 1.5) than the FSH on the suction side of the airfoil.…”
Section: Subscripts and Superscriptsmentioning
confidence: 99%
“…A review of shaped hole geometries found in the literature identified 130 different hole designs. Geometries included conical, laidback, and fanshaped holes [2][3][4][5][6], and many novel designs: bean-shaped [7], cusp-shaped [8], crescent-shaped [9], cratered [10], "Console" [11], double-jet [12], Nekomimi [13], transonic wall jet [14], waist-shaped [15], arrowhead-shaped [16], and anti-vortex holes [17]. The review included not only flat-plate studies, but also endwall, airfoil, and test coupon studies that featured shaped holes [18][19][20].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Shih et al [4] presented a concept of placing a strut within each film cooling hole to modify the vortices structure. Okita and Nishiura [5] proposed an arrowhead-shaped hole for improving film cooling effectiveness. Fric and Campbell [6] introduced the so-called cratered film cooling hole whose shape near the exit region is recessed to a shallow cylinder.…”
Section: Introductionmentioning
confidence: 99%